Effects of varying pretreatment conditions on temperature-phased anaerobic co-digestion of sewage sludge and Chlorella vulgaris - Bondad, Cheassylynne B.
Anaerobic digestion (AD) employs biological degradation of biomass such as solid wastes and wastewaters that can extract methane-rich biogas, a renewable energy source. Temperature-phased anaerobic digestion (TPAD) has recently gained attention due to its capability to improve the hydrolysis stage which is known to be the rate-liming step of AD. The TPAD system involves thermophilic pretreatment with a short retention time (1-3 d) prior to mesophilic anaerobic digestion with a longer retention time (10-20 d). In this study, the effects of varying pretreatment conditions to the degree of solubilisation in the thermophilic stage and methane yield in the mesophilic stage were investigated in order to improve the process of TPAD. Three pretreatment conditions were conducted in laboratory scale using waste activated sludge as substrate: 2d HRT at 65°C, 2d HRT at 75°C, and 3d HRT at 75°C. Sludge samples were taken for pH, chemical oxygen demand (COD), soluble chemical oxygen demand (SCOD), protein, and carbohydrate analyses. Biochemical methane potential tests were performed following each pretreatment condition. Cumulative methane yield was found to be highest (215.73 mL CH4/g VSadded) after pretreatment at 75°C with 2d HRT followed by pretreatment at 65°C with 2d HRT (147.55 mL CH4/g VSadded) and lastly after pretreatment at 75°C with 3d HRT (139.82 mL CH4/g VSad